Reading of musical staff and reading of verbal written language: convergences and divergences - Demicio, Mauro Sergio; Luz, Marcelo Caires; Arena, Dagoberto Buim [UNESP] (Univ Federal Goias, 2020)
In this paper, the objective is to establish relationships between reading texts in written language and reading musical staff, establishing convergences and divergences and starting a debate divided between those who take this act by deciphering and those who take it as an intelligent process about creating senses. The text is aligned with the second group, especially from the contemporary conceptions of music education and the conceptions of art as the only symbolic form capable of making explicit the human feelings in their totality. We have preliminary conclusions that the theoretical approximation of the two acts of reading can provide other perspectives for the teaching-learning process of musical reading.
Keywords: Reading; Written language; Music; Musical staff; Decryption